Analysis of Social Media Opinion on the Representation of the 2024 Presidential Election on Twitter: A Social Network Analysis - Hastuti, Hastuti; Maulana, Harry Fajar; Tompo, Andi Putri Hardiyanti; Ferizka, Zalfa Zarifah (Jurnal Studi Ilmu Pemerintahan, 2023)
This study uses a quantitative approach to analyze netizen discussions on social media about political choices and 2024 Presidential Candidates. The data were collected through online participant observation using the Drone Emprit Academic program and Gephi tools as visualization from September 1, 2022, to December 15, 2022. Social Network Analysis (SNA) was employed as a data-gathering approach by Drone Emprit Academic (DEA), Universitas Islam Indonesia. The study found that degree centrality calculations can be used to identify prominent individuals. The @abu_waras node was identified as having the highest degree centrality value, indicating significant influence within the network. However, its follower rank was low, suggesting that popularity needs to be increased. The @ChsnulCh_ node had a high popularity value but a lower degree centrality value, indicating popularity but insufficient influence in the project. This study highlights the potential of quantitative approaches like SNA for analyzing social media conversations and identifying influential actors. However, it also emphasizes the importance of considering both influence and popularity values when evaluating the significance of individual actors within the network.